Elevation Affects the Development, Growth, and Cocoon Quality of Eri Silkworm Samia cynthia ricini Boisduval (Lepidoptera: Saturniidae) - Nurkomar, Ihsan; Wahyu Trisnawati, Dina; Adi Nugraha, Yudha; Nur Aisyah, Siti; Cahya Endrawati, Yuni (HAYATI Journal of Biosciences, 2025)
Samia cynthia ricini is a species of silkworm whose survival, development, and cocoon quality are affected by its environmental factors such as elevation, which affects temperature and humidity. This study aimed to examine the impact of elevation on the survival, development time, cocoon shell weight, and fecundity of S. c. ricini. The research was performed at two sites with different elevations: highland and lowland regions. The findings indicated that S. c. ricini, reared in the highlands, had higher survival rates than those cultivated in the lowlands. Meanwhile, the developmental time of S. c. ricini reared in the lowlands was faster than in the highlands. Additionally, the cocoon shell weight of S. c. ricini reared in the lowlands was also heavier, and the total fecundity of the adults of S. c. ricini reared in the lowlands was higher than those reared in the highlands. This study recommends that S. c. ricini be reared in lowland settings for best results.